Targeted resequencing reveals high-level mosaicism for a novel frameshift variant in associated with beta-propeller protein-associated neurodegeneration. - Susgun, Seda; Demirel, Mert; Yalcin Cakmakli, Gul; Salman, Baris; Oguz, Kader K; Elibol, Bulent; Ugur Iseri, Sibel Aylin; Yapici, Zuhal (My University, 2023)
Beta-propeller protein-associated neurodegeneration (BPAN) is a rare X-linked dominant neurodegenerative disease, which is characterized by iron accumulation in the basal ganglia. BPAN is associated with pathogenic variation in , which has been reported almost exclusively in females most probably due to male lethality in the hemizygous state.

Whole exome sequencing (WES) and targeted deep sequencing were performed for a male with a clinical diagnosis of BPAN at the age of 37.

The novel frameshift variant in detected by WES was further analyzed with targeted resequencing to detect a mosaic variant with a level of 85.5% in the blood sample of the proband.

Although the main role of remains elusive, recent studies show that may contribute to neurodegeneration through defects in autophagy, iron storage and ferritin metabolism, mitochondria organization, and endoplasmic reticulum homeostasis. The extend of spatiotemporal haploinsufficiency of frameshifting variants caused by mosaicism in males may lead to variable clinical severity, which may be hard to elaborate clinically. Promising genetic analysis strategies using targeted deep sequencing may help determine the clinical outcome of somatic mosaicism in neurological disorders including BPAN. Additionally, we suggest that deep sequencing should be conducted in cerebrospinal fluid samples to provide more reliable results in terms of reflecting the mosaicism level in the brain for future studies.
Keywords: BPAN; WDR45; WES; mosaicism; targeted resequencing